1956
DOI: 10.1172/jci103322
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Preservation. Vii. Acid-Citrate-Dextrose-Inosine (Acdi) as a Preservative for Blood During Storage at 4° C1

Abstract: Previous investigations on erythrocyte preservation (1-4) have demonstrated a marked effect of purine nucleosides on the metabolism of the red cell throughout storage. Attention has been focused upon the effect of adenosine in the maintenance of glucose metabolism and of high energy phosphate compounds, such as adenosine triphosphate (ATP). As a result, not only are the physical and chemical characteristics of the erythrocyte preserved, but the storage period, during which satisfactory post-transfusion viabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
3

Year Published

1957
1957
1982
1982

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 12 publications
0
24
0
3
Order By: Relevance
“…(28). Since improved preservation of stored red cells has been reported after addition of certain purine nucleosides (29)(30)(31), the effects of adenosine and inosine (0.03 to 10 mM) were studied in relation to the development of agglutinability.…”
Section: Stndies Of the Serum Factormentioning
confidence: 99%
“…(28). Since improved preservation of stored red cells has been reported after addition of certain purine nucleosides (29)(30)(31), the effects of adenosine and inosine (0.03 to 10 mM) were studied in relation to the development of agglutinability.…”
Section: Stndies Of the Serum Factormentioning
confidence: 99%
“…Hemolysis during storage was determined by the measurement of plasma hemoglobin as the pyridine he- ' adjusted to pH 10 with NH4OH, according to the methods described previously (1). After identification of the purine-containing compounds with the use of an ultraviolet light (Mineralite), the materials were eluted from the paper with water and measured spectrophotometrically.…”
Section: Methodsmentioning
confidence: 99%
“…Since both hypoxanthine and inosine were present in the plasma of blood stored in ACDI or ACDA (1,4,8), the relative amounts of each substance could not be estimated directly from light absorption measurements alone. However, after the amount of hypoxanthine had been determined by means of xanthine oxidase, it was possible from the light absorption data on the plasma filtrates, to correct the extinction values at 249 m'& (peak light absorption of hypoxanthine, millimolar extinction coefficient 10.5) for hypoxanthine concentration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1955 Gabrio, Donohue, Huennekins and Finch (1) reported that inosine prolonged the period that human blood could be stored at 40 C. in acid citrate dextrose (ACD); their experimental evidence indicated greater than 70 per cent viability of the erythrocytes after six weeks of storage. Because of these encouraging findings, a cooperative study was undertaken in which the posttransfusion survival of erythrocytes from blood stored in ACD and in ACD plus inosine (ACDI) was compared (2).…”
mentioning
confidence: 99%